How to Synchronize Longitudinal Patient Data With the Underlying Disease Progression: A Pilot Study Using the Biomarker CRP for Timing COVID-19 - Maibach, Martina A.; Allam, Ahmed; Hilty, Matthias P.; Perez Gonzalez, Nicolas A.; Buehler, Philipp K.; Wendel Garcia, Pedro D.; Brugger, Silvio D.; Ganter, Christoph C., The CoViD-19 ICU-Research Group Zurich, The RISC-19-ICU Investigators; Krauthammer, Michael; Schuepbach, Reto A.; et al. (Frontiers in Medicine, 2021)
The continued digitalization of medicine has led to an increased availability of longitudinal patient data that allows the investigation of novel and known diseases in unprecedented detail. However, to accurately describe any underlying pathophysiology and allow inter-patient comparisons, individual patient trajectories have to be synchronized based on temporal markers. In this pilot study, we use longitudinal data from critically ill ICU COVID-19 patients to compare the commonly used alignment markers "onset of symptoms", "hospital admission" and "ICU admission" with a novel objective method based on the peak value of the inflammatory marker C-reactive protein (CRP). By applying our CRP-based method to align the progression of neutrophils and lymphocytes, we were able to define a pathophysiological window that improved mortality risk stratification in our COVID-19 patient cohort. Our data highlights that proper synchronization of longitudinal patient data is crucial for accurate interpatient comparisons and the definition of relevant subgroups. The use of objective temporal disease markers will facilitate both translational research efforts and multicenter trials.